Development of clickable approaches to build functional polymeric nanoparticles - Makawitage, Daminda Ayal Perera (2010)
Smart functional nanoparticles have attracted considerable interest over the last few years due to their unique properties and behaviours, which could be used in a wide range of applications such as diagnostics and drug delivery.